Bipolar Ni/ZnO/HfO2/Ni RRAM with multilevel characteristic by different reset bias. (July 2015) - Hsieh, Wei-Kang; Lam, Kin-Tak; Chang, Shoou-Jinn
Abstract: The authors report the fabrication and characterization of resistive random access memory (RRAM) with Ni/ZnO/HfO2 /Ni structure at room temperature. It was found that the proposed device exhibited bipolar switching behavior with multilevel characteristics in a reset process. It was found that the device exhibited two-step reset stage under high reset bias. By applying a 2nd reset stage after the transformation of the 1st reset stage, it was found that the RRAM could return to the initial state. From I – V curves measured in these two reset stages, it was found that the current conduction was dominated by Schottky emission due to the migration of oxygen ions and recombination with oxygen vacancies. This reaction could break the conducting filament so as to transform carrier transport mechanism to Schottky emission. This also results in the simultaneous transformation from low resistance state (LRS) to high resistance state (HRS).